Acute Agitation and Self-Injury in a 5-Year Old with Autism. Issue 7 (September 2016) - Schweitzer, Jason; James, Christine; Jenkins, Willough; Reiff, Michael I.; Stein, Martin T.
Abstract : CASE: A 5-year-old nonverbal child with autism spectrum disorder (ASD) was admitted to inpatient pediatrics with new onset agitation and self-injurious behavior. His parents described him as a pleasant child without previous episodes of self-injury. Four days before admission, the parents noted new irritability followed by 2 days of self-injury to the face without clear precipitant. His hitting intensified with closed fist to face, and he required parental physical restraint to prevent further injury. Car rides and ibuprofen provided only temporary relief. He consumed minimal liquid and ate no solid food for 2 days. The parents denied any changes to the environment or routine and denied recent travel, sick contacts, fevers, cough, otalgia, vomiting, diarrhea, and constipation. The patient had been diagnosed with ASD at age 18 months old but had no other significant medical history. On examination, the child was alert but distressed and restless, wearing padded mitts as his parents attempted to calm him by pushing him in a stroller. He had multiple areas of severe bruising and facial swelling in the right periorbital area, cheek, and jaw. The rest of the physical examination was unremarkable. Laboratory results included a leukocytosis with left shift, a normal metabolic panel, and an elevated creatine kinase. Other investigations included a normal lumber puncture, chest radiograph, head and face computerized tomography without contrast, and brain magnetic resonance imaging. A dentist consultant examined him and noted an erupting molar but no decay or abscesses. A psychiatric evaluation was requested as there was no clear medical source for the patient's distress.